LC-MS/MS analysis of 11-nor-9-carboxy-hexahydrocannabinol (HHC-COOH) and 11-hydroxy-hexahydrocannabinol (HHC-OH) for verification of hexahydrocannabinol (HHC) intake - Pettersson-Pablo, Paul; Oxelbark, Joakim (Scandinavian journal of clinical and laboratory investigation, 2024)
Natural and semi-synthetic cannabinoid analogs are getting increasing media attention for their recreative use as an alternative to traditional cannabis, in Sweden as well as internationally. To investigate an increasing number of urine samples incoming to our clinical laboratory that were screening positive, using a CEDIA THC-COOH immunoassay from ThermoFisher Scientific, but then testing negative using GC-MS based verification analysis, we developed an LC-MS/MS-method for verification of hexahydrocannabinol (HHC) and Δ8-tetrahydrocannabinol. Assessment of HHC intake was based on identification of the following four metabolites: 11-nor-9(R)-carboxy-hexahydrocannabinol (R-HHC-COOH), 11-nor-9(S)-carboxy-hexahydrocannabinol (S-HHC-COOH), 11-hydroxy-9(R)-hexahydrocannabinol (R-HHC-OH) and 11-hydroxy-9(S)-hexahydrocannabinol (S-HHC-OH). Out of 46 urine samples analysed in this study, 44 showed presence of HHC-metabolites, which indicate HHC as the main explanation for an increased number of negative verifications for THC-COOH. In these samples, the HHC-OH metabolites occurred at a higher concentration than R-HHC-COOH while S-HHC-COOH was only detected in few samples at low concentrations. R-HHC-COOH and S-HHC-COOH can easily be added to a pre-existing verification method for THC-COOH, and still show acceptable results, while HHC-OH requires an enzyme capable of hydrolysing the ether glucuronide bond.